The five levels of leadership : proven steps to maximize your potential - Maxwell, John C., 1947- (New York : Center Street, 2011)
True leadership isn't a matter of having a certain job or title. In fact, being chosen for a position is only the first of the five levels every effective leader achieves. To become more than "the boss" people follow only because they are required to, you have to master the ability to invest in people and inspire them. To grow further in your role, you must achieve results and build a team that produces. You need to help people to develop their skills to become leaders in their own right. And if you have the skill and dedication, you can reach the pinnacle of leadership-where experience will allow you to extend your influence beyond your immediate reach and time for the benefit of others. The 5 Levels of Leadership are: 1. Position - People follow because they have to. 2. Permission - People follow because they want to. 3. Production - People follow because of what you have done for the organization. 4. People Development - People follow because of what you have done for them personally. 5. Pinnacle - People follow because of who you are and what you represent. Through humor, in-depth insight, and examples, internationally recognized leadership expert John C. Maxwell describes each of these stages of leadership. He shows you how to master each level and rise up to the next to become a more influential, respected, and successful leader. - Publisher.
You can have a leadership game plan for your life : You can learn practical leadership tools ; Overview of the 5 levels of leadership ; Insights into the 5 levels of leadership -- Leadership assessment: how to gauge your current level of leadership -- Level 1. Position : It's a great place to visit, but you wouldn't want to live there : The upside of position: you have been invited to the leadership table ; The downside of position: true leadership isn't about position ; Best behaviours on level 1: how to make the most of your position ; The laws of leadership at the position level: lid, process, and navigation ; Beliefs that help a leader move up to level 2 ; Guide to growing through level 1 -- Level 2. Permission : You can't lead people until you like people : The upside of permission: the workplace has become more pleasant for everyone ; The downside of permission: the pressure is on you to build positive relationships ; Best behaviors on Level 2: how to gain people's permission ; The laws of leadership at the permission level: influence, addition, solid ground, magnetism, connection, and buy-in ; Beliefs that help a leader move up to level 3 ; Guide to growing through level 2 -- Level 3. Production : Making things happen separates real leaders from wannabes : The upside of production: you now have leadership credibility ; The downside of production: the weight of leadership just got heavier ; Best behaviors on level 3: how to make the most of production in leadership ; The laws of leadership at the production level: respect, magnetism, picture, victory, Big Mo, priorities, sacrifice, and buy-in ; Beliefs that help a leader move up to level 4 ; Guide to growing through level 3 -- Level 4. People development : Helping individual leaders grow extends your influence and impact : The upside of prople development: the potential of the organization just got greater ; The downside of people development: leading on level 4 requires high levels of maturity and skill ; Best behaviors on level 4: how to develop people ; The laws of leadership at the people development level: process, addition, inner circle, empowerment, explosive growth, and buy-in ; Beliefs that help a leader move up to level 5 ; Guide to growing through level 4 -- Level 5. The pinnacle : The highest leadership accomplishment is developing other leaders to level 4 : The upside of the pinnacle: your influence has expanded beyond your reach and your time ; The downside of the pinnacle: you may start to believe it's all about you ; Best behaviors on level 5: how to use the pinnacle as a platform to do something greater than yourself ; The laws of leadership at the pinnacle level: respect, intuition, timing, legacy, and explosive growth ; Help others move up to levels 4 and 5: create crucible moments for the leaders you develop ; Guide to being your best at level 5 -- Portrait of a Level 5 leader : Coach John Wooden.
Includes bibliographical references.
Keywords: Leadership